Positive Negative Economic Impact of Covid-19 and Macroeconomic Policy on Industry, Business Sector in Indonesia - Musriha; Daud, Nahu; Wuryani, Eny; Holisin, Iis; Fatihudin, Didin; Sembiring, Murpin J. (Sinergi International Journal of Economics, 2025)
This paper present the result of analysis that economic impact of Covid-19 on industrial prices/commodities, the business sector in Indonesia is not all negative, but there are also positives. WFH policy, social distancing, physical distancing, #dirumahaja, many people do not leave the house, negatively impact the inhibition of the distribution channel of goods/services. from upstream to downstream, from supplier to manufacturer, distributor to consumer. But there are certain sector companies that have a positive impact on their financial performance even though they are not as big as when normal, especially those based on virtual, pharmaceuticals and food. The methods used in this study are descriptive and expost facto. The resurt of this study in indonesian macroeconomic policies in the face of covid-19 economic stabilization, in the form of interest rate subsidies, tax rates, social assistance, direct cash assistance (BLT), low-cost staples. Lower banking rates, lower income tax rates, ease of provision of basic materials. Delays in paying credit installments (principal and interest), easier provision of capital for medium-small enterprises (SMEs), micro-empowerment capital, to increase banking capital, control prices, avoid inflation. Delays in paying credit installments (principal and interest), easier provision of capital for medium- small enterprises (SMEs), micro-empowerment capital, to increase banking capital, control prices, avoid inflation. The limitation this study needs many sampling and objective analysis for sectors affect by covid 19.